Estudo dos efeitos da gamificação na motivação e na memorização de estudantes de medicina em cenário de prática laboratorial de anatomia humana - Vieira, Diogenes Coelho (2020)
Introduction: The teaching of Human Anatomy in the first term of medical school is challenging and, occasionally, demotivating, given its high theoretical-practical burden and its distance from clinical practice. Due to its importance for the training of doctors, there has been considerable effort for methodological changes in the last decades, with a view to develop a new teaching-learning process, student-centred and supported by the teacher as a facilitator and mediator in the process. In this context, educators have been seeking after alternatives for new practices. Among them, gamification stands out, which consists in the implementation of fundamental characteristics of games, within an educational setting, which are capable of positively influencing students' motivation, attention, understanding, memorisation, and metacognition, rendering meaningful learning outcomes. Objectives : To evaluate the effects of the inclusion of gamification in laboratory lessons of Human Anatomy in relation to the motivation of medical students in addition to short and long-term memorisation. Methodology: a transversal experimental research with 41 subjects in their first term as medical school students at UNIFENAS-BH, in the first semester of 2019, who were taking the Human Anatomy course. The participants attended a mini class, being subsequently and randomly divided into two groups, one of which proceeded with a traditional laboratory class whereas the other participated in a gamified laboratory class. A card-based game model was used; it was a specific educational game developed to be used for the purpose of this work (ANATOCARD). During the intervention, students were evaluated by doing pre-tests (pre-test, post-test 1, post-test 2 and post-test 3) and by completing an IMMS questionnaire to assess their motivation. Seven days after doing post-test 2, students did post-test 3, without previous notice. Conclusion: An educational game was developed - a gamified educational object - which was named ANATOCARD. The game proved to be useful, making it possible to reach the goals of this research, in addition to being reproducible and inexpensive, which easing its diffusion. In the group where gamification was added, compared to the control group, we observed a higher, statistically significant, motivation level, which was noticeable in all of its dimensions (Attention, Relevance and Satisfaction), not only Trust. Regarding proficiency, results show an adequate correspondence among the effects of gamification, fully comparable to those of the traditional methods of teaching Anatomy. Furthermore, students in the gamification-group showed greater knowledge retention in post-test 3, with statistical significance. Therefore, the results of this work make it possible to conclude using this gamified educational object as a valid alternative for teaching Human Anatomy to medical school students